If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -32 + 9 = -14 + -11x Combine like terms: -32 + 9 = -23 -23 = -14 + -11x Solving -23 = -14 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -23 + 11x = -14 + -11x + 11x Combine like terms: -11x + 11x = 0 -23 + 11x = -14 + 0 -23 + 11x = -14 Add '23' to each side of the equation. -23 + 23 + 11x = -14 + 23 Combine like terms: -23 + 23 = 0 0 + 11x = -14 + 23 11x = -14 + 23 Combine like terms: -14 + 23 = 9 11x = 9 Divide each side by '11'. x = 0.8181818182 Simplifying x = 0.8181818182
| 4x+5x-12=(-3x)+24 | | (x-7)2=9 | | 45=x-4x | | -6x+24=54 | | -5+z=14-37 | | -9.4x=47.0 | | -5+2=14-37 | | x+5-8=-4 | | -4x^2+24=32 | | -7(3b+3)+(22b-4)=0 | | 9(2x-6)=3(6x+5) | | n-3n=-14-4n | | 9+3z-3=9z+12-3z | | 9+3z-3=9z+122-3z | | 3.9q-1.9-4.3q=-1.4q-5.5 | | 5(5+t)-3(t-6)= | | x(5x+1)(x-9)=0 | | 3(2n-7)+7(4-2n)= | | x^2-6x+20=0 | | 124-6x=21x+16 | | 3/2(5x-2)=x | | 3(x+4)+2(5x+2)= | | 6x+7+3x+1= | | -4x+5=5-4x | | -3y+6=-4y+7 | | 7xy-xy+3xy= | | 4w-5+9w+2= | | -4+5=5-4x | | 20-x=10x-2 | | 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 |